The impact of special autonomy on Papua’s forestry sector: empowering customary communities (masyarakat adat) in decentralized forestry development in Manokwari district - Tokede, M.J.; Wiliam, D.; Widodo; Gandhi, Y.; Imburi, C.; Patriahadi; Marwa, J.; Yufuai, M.C. (Center for International Forestry Research, 2005)
The report focuses on the impacts of special autonomy in Papua on the forestry sector. It studies the advantages and problems associated with the current forestry management system. The most significant change following special autonomy for Papua was the introduction of small-scale concession permits granted to community cooperatives, locally known as Kopermas. As a result, CIFOR and the State University of Papua’s research focused on these Kopermas, analyzing data on timber production and revenues from concessions, and determining the flow of benefits to customary communities’ incomes and to regional revenues. The objective was to determine how effectively the Kopermas system has empowered local communities. Using a combination of conventional and participatory/action research methods, the research team evaluated the livelihoods and environmental value of forest resources for local people. We also facilitated stakeholder input into our research findings and analysis. The team also worked with local communities to determine their current capacity for forest management; which mechanisms were used to distribute the benefits from the new system; and how people were involved in decision-making about permit applications and concession management. This research found some direct involvement of local people in forest management and short-term benefits for local communities. However, we also found that the benefits from timber revenues have not been fairly shared among local people and other actors involved in the timber business. As a result, community forestry cooperatives have yet to contribute to equitable and sustainable development for local people. To improve this situation, local stakeholders identified an urgent need to empower customary organizations and individuals by equipping them to manage their own natural resources independently. This will reduce the likelihood that communities are exploited by more powerful stakeholders in the future. Alongside low capacity, facilities and skills for commercial forest management, challenges included low levels of information about government policy, unclear and inconsistent regulations and implementing guidelines, lack of recognition of communities’ rights, and lack of capital for investment. Local people concluded that government institutions and local stakeholders should take a more proactive role to provide the necessary assistance and advice. The government needs to issue and socialize policies with practical and applicable sanctions for non-compliance and to facilitate local involvement in policy making regarding permit issuance and provincial and district spatial planning processes. Coordination and cooperation among the relevant institutions and organizations could also be improved.